Knowledge management yesterday and tomorrow: exploring an ‘Intellectual Paradox’ - Maindze, Alexslis; Jennions, Ian K.; Skaf, Zakwan (IOS Press, 2017)
Knowledge management continues to be characterized by strong contextual application with diversity of techniques, tools and applications which practitioners far and wide seem to agree and adopt. However, when it comes to its philosophical distinctness, it is yet to achieve something as seemingly easy as a common definition. There is significant agreement on fluidity and methods of application but limited consensus on philosophical interpretation. Furthermore, that we know what it is, acknowledge its impact, functional relevance and yet cannot articulate a common methodology points to what this paper terms an ‘intellectual paradox’. An intellectual paradox is the phenomenon whereby professionals and academics acknowledge a concept, practice it, write about it, and promote its relevance individually but as a collective lack a consensus on exactly what it is. This paper seeks to explore this phenomenon in detail and to propose a philosophical framework. It further explores the role of the traditional composition; people, process and technology in sustaining this suggested conundrum. This phenomenon seems to tie neatly with the tacit form of knowledge on the basis of the difficulty in articulating a common definitional framework of perception, though it could be argued that it is merely exhibiting characteristics of ‘Tacit’ knowledge management; thereby justifying the status quo. Some authors point to “descriptive frameworks” and insufficient addressing of learning including structural differences in organisations. This difficulty per some writers, results from the use of multiple and variable methods, tools techniques and strategies. Their alternative proposition views for a both ‘descriptive and prescriptive’ framework still did not yield a consensus either. This paper seeks to explore the problem and to propose a new definition.